Implementation of Math Games to Develop Students’ Motivation in Solving Numeracy Problems - Djamilah, Soraya; Ulfah, Fithria (Universitas Ahmad Dahlan, 2025)
The numeracy skills of students in Indonesia are still low. Therefore, researchers implemented mathematics games in mathematics learning to foster students' motivation in solving numeracy problems. The math games implemented include the 3-6-9 game, mission X, mathematical snakes and ladders, and role play. The aim of this research is to find out how to implement mathematical games by referring to the implementation of David C. Korten's model in its application by increasing students' motivation in solving numeracy problems. This research used descriptive qualitative. The subjects were students at SDN Pemurus Dalam 6. Data was collected through interviews, observation, and documentation. The results show that based on the implementation model, this math games program is appropriate, both in terms of the program, program users, and program implementing organization. The implementation of this math games has been successfully implemented and can increase students' motivation in solving numeracy problems.